2016
DOI: 10.2144/000114484
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Capture and Sequencing of Gene-Sized DNA Molecules

Abstract: Targeted capture provides an efficient and sensitive means for sequencing specific genomic regions in a high-throughput manner. To date, this method has mostly been used to capture exons from the genome (the exome) using short insert libraries and short-read sequencing technology, enabling the identification of genetic variants or new members of large gene families. Sequencing larger molecules results in the capture of whole genes, including intronic and intergenic sequences that are typically more polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…The methodology takes advantage of the focused re-sequencing of NLRs through RenSeq (Jupe et al, 2013). RenSeq has previously been used for improving genome annotations and genetic mapping of plant NLRs (Chen et al, 2018;Jupe et al, 2013), the prioritisation of novel NLRs in wild diploid species (Jiang et al, 2018;Van Weymers et al, 2016), and identification of candidate NLRs when combined with long-read sequencing technology (Giolai et al, 2016;Witek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The methodology takes advantage of the focused re-sequencing of NLRs through RenSeq (Jupe et al, 2013). RenSeq has previously been used for improving genome annotations and genetic mapping of plant NLRs (Chen et al, 2018;Jupe et al, 2013), the prioritisation of novel NLRs in wild diploid species (Jiang et al, 2018;Van Weymers et al, 2016), and identification of candidate NLRs when combined with long-read sequencing technology (Giolai et al, 2016;Witek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches, for example, have been successfully applied to investigating R-gene variation in crop plants (Jupe et al, 2012(Jupe et al, , 2013Andolfo et al, 2014;Giolai et al, 2016;Russell et al, 2016;Van Weymers et al, 2016). Whole genome resequencing approaches could be useful for setting the genomic context and fate of duplications, but there are still substantial challenges to resolve in distinguishing loss of copies from lack of coverage or lack of assembly to the reference due to high sequence divergence.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…For example, the "big bang" theory of the emergence of the adaptive immune systems in vertebrates invokes multiple rounds of WGD as the major source of this potential (Flajnik and Kasahara, 2010). Similarly, investigation of the genomic repertoire of pathogen-associated genes (R genes) in several crop plants through targeted sequence capture (Jupe et al, 2012(Jupe et al, , 2013Giolai et al, 2016;Van Weymers et al, 2016) has revealed much more extensive gene families than was previously predicted based on whole genome resequencing studies. R genes have also been demonstrated to show signatures of adaptive introgression between closely related species of Arabidopsis, with extensive trans-specific sharing of alleles across species (Bechsgaard et al, 2017).…”
Section: Introduction Background and Aimsmentioning
confidence: 99%
“…These approaches were initially developed for targeted sequencing of protein-coding regions of genomic DNA (whole exome sequencing) 13 and RNA fragments from short-read RNA-seq experiments (e.g., CaptureSeq) [14][15][16][17][18] . Such approaches have been adapted for targeted sequencing of long genomic fragments (>2kb) or full-length cDNA molecules [19][20][21][22][23][24] . In two notable studies described recently, complex pools of biotinylated oligos were used to enrich for and sequence thousands of protein-coding and lncRNA targets, leading to considerable gains in isoform detection and new insights about the nature of transcriptomic complexity 25,26 .…”
Section: Introductionmentioning
confidence: 99%